Stability of evolutionary brittle-tension 2D solids with heterogeneous resistance. (1st October 2016) - Baratta, Alessandro; Corbi, Ileana; Corbi, Ottavia
Highlights: The problem of modeling and analysis of masonry continua is focused on. An original formulation is proposed accounting for a reduced tensile resistance. The evolutionary character in time of the material behavior is embedded. Abstract: Modeling and analysis of masonry continuum through mechanical models that embed some low tensile skill of the masonry and account for its decay process during time is rarely treated in literature. More sophisticated models are to be considered able to produce results in major agreement with real data. The development of theoretical formulations aimed at a priori producing evaluations about the overall performance of these models have a central importance, since they allow to make reasoned computational choices about the mechanical models to be referred to for computations. In this paper one focuses on a special mechanical model for masonry bodies, which is referred to as Elastic Brittle tension (EB) model. Actually the EB model is evolutionary since the non-null tensile stress yield value is assumed to decay during time and converge towards the No-Tension behavior. This involves the need of investigating the relationships of the solution with other solutions related to more known mechanical models, which requires for the EB model the development of a proper theoretical formulation that is presented in the paper. One starts from the consideration that in this case, since the failure in tension is brittle, the theorems of Limit Analysis (LA) are not justified. Thereafter one sets up an approach to the problem aimed at investigating how far the collapse behavior of EB structures can be analyzed through the usual LA tools; some bounding thresholds for their ultimate load-carrying capacity with some original stability statements are then formalized. The proposed approach is here referred to masonry arches modeled under the EB hypothesis but it may be easily generalized to different structural typologies.